The Role of Dance Education in Strengthening Pancasila Values: Evidence from Indonesian Educational Literature - Sama Etika Berutu; Helena Petronella Sirait; Annisa Kirani Putri; Habibi Habibi; Sri Yunita (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: This systematic review examines the role of dance education in strengthening Pancasila values among Indonesian students across formal educational settings. The study synthesizes empirical and qualitative evidence from Indonesian scholarly literature to determine how dance-based pedagogical approaches facilitate the internalization of Indonesia's five foundational national principles. Materials and methods: Following the PRISMA 2020 framework, a systematic search was conducted across four major databases—Scopus, Web of Science (WoS), ERIC, and Google Scholar—covering publications from January 2014 to December 2024, executed between January 15 and March 1, 2025. Boolean search strings combined terms for dance education (seni tari, tari tradisional), Pancasila values, and Indonesian educational contexts. Of 1,285 initially identified records, 35 peer-reviewed studies met all eligibility criteria and were included in the final synthesis. Results: Analysis revealed that dance education significantly contributes to all five Pancasila dimensions. The strongest evidence was found for national unity and cultural identity (Sila 3; n=15 studies) and religiosity and spiritual awareness (Sila 1; n=12 studies). Effect sizes ranged from small (d=0.32) to large (d=1.14), with most studies reporting statistically significant improvements (p<0.05). Five recurring pedagogical mechanisms were identified: cultural embodiment, collaborative choreography, reflective practice, community performance, and symbolic ritual enactment. Conclusions: Dance education constitutes a culturally congruent and evidentially robust medium for Pancasila values transmission in Indonesian schools. Curriculum designers, policymakers, and educators should integrate structured dance programs across educational levels to support national character-building objectives. Future research should address longitudinal outcomes and cross-regional comparisons.